Optimizing COVID-19 testing capabilities and clinical management using pathology informatics. Issue 4 (5th December 2020) - Chamala, Srikar; Flax, Sherri; Starostik, Petr; Cherabuddi, Kartikeya; Iovine, Nicole M; Majety, Siddardha; Newsom, Kimberly J; Reeves, Mary; Joshi-Guske, Michael J; Downey, Maggie M; Lele, Tanmay P; Clare-Salzler, Michael J
Abstract: Coronavirus disease 2019, first reported in China in late 2019, has quickly spread across the world. The outbreak was declared a pandemic by the World Health Organization on March 11, 2020. Here, we describe our initial efforts at the University of Florida Health for processing of large numbers of tests, streamlining data collection, and reporting data for optimizing testing capabilities and superior clinical management. Specifically, we discuss clinical and pathology informatics workflows and informatics instruments which we designed to meet the unique challenges of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing. We hope these results benefit institutions preparing to implement SARS-CoV-2 testing.